THE USE OF SCAFFOLDING IN TEACHING WRITING : Pre-experimental Study of Grade X Students at SMK Budhi Cendekia Bandung - Yusuf, Daud (2014)
Penelitian ini mengkaji penggunaan scaffolding dalam pembelajaran menulis. Penelitian ini bertujuan untuk mengetahui apakah penggunaan scaffolding berkontribusi terhadap peningkatan kemampuan siswa dalam menulis teks recount serta mengetahui pendapat siswa mengenai penggunaan scaffolding dalam pembelajaran menulis. Penelitian ini menggunakan desain explanatory sequential, dimana studi eksperimental digunakan sebagai fase kuantitatif diikuti studi deskriptif sebagai fase kualitatif. Dalam fase kuantitatif, 20 orang siswa terlibat sebagai sampel dalam kelompok eksperimen. Sedangkan dalam fase kualitatif, penelitian ini menggunakan analisis dokumen dan wawancara sebagai pendukung hipotesis. Uji hipotesis menunjukan bahwa skor post-test (M = 2.35, SD = .745) lebih tinggi daripada skor pre-test (M = 2.00, SD = .649) , dengan t(19) = -2.666, p < .05, r2 = .272. Nilai effect size menunjukkan bahwa intervensi mempenyai kontribusi yang besar terhadap peningkatan kemampuan siswa, didukung dengan hasil analisis teks siswa yang menunjukkan indikasi serupa. Hasil wawancara menunjukkan bahwa penggunaan scaffolding telah membantu siswa dalam menguasai keterampilan menulis. Kata kunci: scaffolding, pembelajaran, menulis The study investigates the use of scaffolding in teaching writing. It aims to investigate whether the use of scaffolding contributes to the improvement of students' writing performance in writing recount texts. The study is also aimed at finding out the way students perceive the use of scaffolding in teaching writing. The study used a sequential explanatory design. It used experimental study as quantitative strand then followed by descriptive study as qualitative strand. In quantitative phase, the study involved a class consisting of 20 students as the experimental group. The data were obtained from seven meetings of teaching program. Therefore, in qualitative phase, the study used document analysis and interview to support the hypothesis testing result. Hypothesis testing revealed that the post-test score (M = 2.35, SD = .745) was significantly higher than the pre-test score (M = 2.00, SD = .649), in t(19) = -2.666, p < .05, r2 = .272 in 2-tailed direction. The effect size was also considered as large (r2 > .25), which indicated that the intervention had a large impact to the students' score. The analyses of student texts demonstrated that the use of scaffolding in teaching writing led to the improvement of students' writing performance. The findings of interview showed that the use of scaffolding helped students to master writing skill. Keywords: scaffolding, teaching, writing